The effectiveness of strategies used by teachers to manage disruptive classroom behaviors: A case study at a religious school in Rawang, Selangor - Wan Yusoff, Wan Mazwati; Mansor, Norwati (IIUM Press, 2016)
Studies have indicated that there is a positive correlation between disruptive behaviors and low academic achievement which resulted in other problems such as absenteeism, school drop-out and delinquent behaviors. Lack of knowledge and skills and failure in managing classroom disruptive behaviors have caused frustration, stress and burnout among teachers which pushed teachers to leave the profession especially novice teachers. The pervasiveness of classroom disruptive behaviors implied that strategies employed by teachers to manage disruptive behaviors are not effective. This requires immediate attention and action to find effective solutions. Therefore, this exploratory study attempts to discover the common classroom disruptive behaviors; to identify strategies used by teachers in managing misbehaviors; and to find out to what extent the strategies used by teachers were actually effective in managing classroom disruptive behaviors. This is especially critical in religious schools since the majority of teachers teaching in religious schools in the state of Selangor had no formal training in education; and they were not trained in classroom management, thus have no exposure on handling student classroom disruptive behaviors. Participants of this study were 14 teachers from a religious school in the district of Rawang, Selangor. Data collected using self-constructed instrument and semi-structured interviews were analyzed using descriptive statistics and qualitative analysis. Findings of this study revealed that majority of classroom disruptive behaviors were low-level disruptions; nonetheless they were burdensome to teachers which led to teacher frustration. Majority of teachers used ineffective punitive measures to handle student misbehaviors. Implications from the study were discussed.